Chondroprotective Effects of 4,5-Dicaffeoylquinic Acid in Osteoarthritis through NF-κB Signaling Inhibition - Goeun Jang; Seul Ah Lee; Joon Ho Hong; Bo-Ram Park; Do Kyung Kim; Chun Sung Kim (MDPI AG, 2022)
Osteoarthritis (OA) is characterized by cartilage degradation, inflammation, and pain. The dicaffeoylquinic acid (diCQA) isomer, 4,5-diCQA, exhibits antioxidant activity and various other health-promoting benefits, but its chondroprotective effects have yet to be elucidated. In this study, we aimed to investigate the chondroprotective effects of 4,5-diCQA on OA both in vitro and in vivo. Primary rat chondrocytes were pre-treated with 4,5-diCQA for 1 h before stimulation with interleukin (IL)-1β (5 ng/mL). The accumulation of nitrite, PGE2, and aggrecan was observed using the Griess reagent and ELISA. The protein levels of iNOS, COX-2, MMP-3, MMP-13, ADMATS-4, MAPKs, and the NF-κB p65 subunit were measured by Western blotting. In vivo, the effects of 4,5-diCQA were evaluated for 2 weeks in a destabilization of the medial meniscus (DMM)-surgery-induced OA rat model. 4,5-diCQA significantly inhibited IL-1β-induced expression of nitrite, iNOS, PGE2, COX-2, MMP-3, MMP-13, and ADAMTS-4. 4,5-diCQA also decreased the IL-1β-induced degradation of aggrecan. It also suppressed the IL-1β-induced phosphorylation of MAPKs and translocation of the NF-κB p65 subunit to the nucleus. These findings indicate that 4,5-diCQA inhibits DMM-surgery-induced cartilage destruction and proteoglycan loss in vivo. 4,5-diCQA may be a potential therapeutic agent for the alleviation of OA progression. In this study, diclofenac was set to be administered once every two days, but it showed an effect on OA. These results may be used as basic data to suggest a new dosing method for diclofenac.